Developing biology students’ worksheet based on STEAM to empower science process skills - Indri Patresia; Melva Silitonga; Aminata Ginting (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Students’ worksheets, as learning material, is important to achieve learning outcomes. This study aimed to develop students’ worksheet, based on STEAM (Science, Technology, Engineering, Art, and Mathematics), on ecosystem topics to empower students’ science process skills. The Research and Development used 4D model by Thiagarajan. Students’ worksheet validity was determined by conducting expert appraisal consisting of instructional review (material and learning expert) and technical review (biology teacher). The product trial was carried out by testing the science process skills of tenth graders. The students’ science process skills were measured using pre-test and post-test, which then were analyzed using N-gain calculation. The results showed that the students’ worksheet based on STEAM was categorized as feasible (material expert) and highly feasible (learning expert and teacher). The N-gain score of students’ science process skills after using student worksheet based on STEAM was 0.5 which categorized as medium. It can be concluded that the students’ worksheet developed is feasible and able to empower the students’ science process skills.